(untitled) (Journal of Society of Surgeons of Nepal, 2016)
Introduction: The advent and rapid acceptance of laparoscopic surgery led to the idea of performing laparoscopic appendectomy (LA). In 1983 Semm, a German gynecologist performed the first LA. More than three decades later, the benefits of LA are still controversial. The objective of this study is to assess the feasibility of laproscopic appendectomy in appendicitis and appendicular perforation. Methods: Thirty five patient undergoing laproscopicappendectomy for appendicitis from 14th feb 2015 to 11th feb 2016 in Grande international hospital were included in the study. Duration of surgery, requirement of analgesia, time to normal diet and regular activity as well as length of hospital stay and postoperative complications were studied. Results: A total of 35 patients underwent laparoscopic appendectomy during the study period.Ten patients have peri-appendicular pus collection of which six patients have perforation. Median duration of surgery was 59±8.64 minutes. Mean Post operative pain score was 4.71±0.71. Mean intravenous fevastin requirement was 3.31±0.9 gm and intravenous ketorolac was 94±27mg while oral diclofenac was 731±172.81mg. Postoperative complications were 9%. Mean time to normal diet resumption was 1.17±0.47 days and time to normal activities was 10.5±2.44 days. Median length of hospital stay was 1.9±0.96 days. Conclusion: Laproscopic appendectomy is a feasible option for appendicitis as well as appendicular perforation. More frequent use of this procedure may lead to reduction in operating time. Continuation of laproscopic appendectomy as a therapeutic option for patients with appendicitisas well as appendicular perforation need evaluation in large study scale.